Assessing the efficiency of maggot production, nutritional value, and frass quality from different organic waste materials - Jupesta Joni; Permana Indra; Sahari Bandung (BIO Web of Conferences)
The larvae of the Black Soldier Fly (BSF), commonly known as maggots, could act as effective agents for decomposing organic waste and produce economically valuable by-products. This study aims to assess the performance of various organic waste feedstocks in producing maggots in terms of yield, nutritional value, and quality of frass. The study was conducted at the Faculty of Agriculture’s screen house and laboratory, Siliwangi University started from February 2024 to June 2024. The research involved systematic experimentation with various organic waste types, including vegetable, fruit, restaurant, and mixed waste (a mixture of fruit, vegetable waste). Each treatment was replicated 5 times. The result showed a significant difference in maggot yield at 14 and 21 days after hatching (DAH) but no difference at 28 DAH. The maggot growth treatment using vegetable waste media showed the highest maggot yield at 14 DAH, while at 21 DAH, the highest maggot yield was observed in the restaurant waste and mixed media treatments. Different organic waste as growth media showed a significant difference in maggot nutritional value, such as water content, ash content, crude protein, crude fat, and carbohydrate (by difference). Maggots reared on mixed waste had the highest protein content, though not significantly different from those reared on vegetable waste. In contrast, maggots from fruit waste had the lowest protein content. The analysis results showed that BSF frass had different nutrient contents of nitrogen (N), phosphorus (P), and potassium (K) for each organic waste treatment. Selecting suitable organic waste for maggot cultivation enhances protein yield, making maggots a viable alternative protein source for animal feed. This process also promotes efficient food waste recycling and organic fertilizer production, supporting sustainable agriculture.